Acetoacetate promotes the formation of fluorescent advanced glycation end products (AGEs). Issue 12 (1st December 2016) - Bohlooli, Mousa; Ghaffari-Moghaddam, Mansour; Khajeh, Mostafa; Aghashiri, Zohre; Sheibani, Nader; Moosavi-Movahedi, Ali Akbar
Abstract : Acetoacetate (AA) is an important ketone body, which produces reactive oxygen species (ROS). Advanced glycation end products (AGEs) are defined as final products of glycation process whose production is influenced by the levels of ROS. The accumulation of AGEs in the body contributes to pathogenesis of many diseases including complications of diabetes, and Alzheimer's and Parkinson's disease. Here, we evaluated the impact of AA on production of AGEs upon incubation of human serum albumin (HSA) with glucose. The effect of AA on the AGEs formation of HSA was studied under physiological conditions after incubation with glucose for 35 days. The physical techniques including circular dichroism (CD) and fluorescence spectroscopy were used to assess the impact of AA on formation and structural changes of glycated HSA (GHSA). Our results indicated that the secondary and tertiary structural changes of GHSA were increased in the presence of AA. The fluorescence intensity measurements of AGEs also showed an increase in AGEs formation. Acetoacetate has an activator effect in formation of AGEs through ROS production. The presence of AA may result in enhanced glycation in the presence of glucose and severity of complications associated with accumulation of AGEs.